The Orientation and Mobility Specialist and Braille: Point–Counter Point Arguments for and Against the Need for the Knowledge of Braille. (March 2020) - Penrod, William M.; Griffin-Shirley, Nora; Hollinger, Kevin; Burgin, Ximena; Smolka, Samantha; Okungu, Phoebe A.; Steinle, Kyle J.; Obiero, Nereah A.
Introduction: Few academic discussions are more contentious in the field of orientation and mobility than the notion of whether or not O&M specialists need to know braille. To help answer this question, we developed a survey. Methods: An online survey instrument was distributed through O&M electronic discussion groups. The survey included a demographic section, a section concerning the use of braille for instructional purposes, questions about the importance of braille in the training and certification of O&M specialists, the level of knowledge of braille required, and whether or not respondents considered braille an essential job function. Results: Most participants ( n = 108) believed or strongly believed that braille should be a separate course in personnel preparation programs and should be required for O&M personnel preparation programs accredited by the Association for Education and Rehabilitation of the Blind and Visually Impaired (AER). Slightly less than half (42%) of respondents believed or strongly believed that braille should be required for Academy for Certification of Vision Rehabilitation and Education Professionals (ACVREP) certification in O&M ( n = 80; 22 respondents were undecided).Discussion: The field of visual impairment (i.e., blindness or low vision) needs to examine closely the amount of time, number of personnel required, and financial cost of pursuing braille as a competency for O&M specialists. Personnel costs may include additional resources to assist ACVREP in changing its requirements to include braille and the revision of the examination to reflect this new requirement, universities in hiring faculty to develop new programs of study to include coursework involving braille, and AER's Higher Education Accreditation Commission in changing the AER University Review Accreditation Curricular Standards: Orientation and Mobility Specialists. Implications for practitioners: This study provided a snapshot of what a group ( N = 189) of vision professionals believe regarding the importance of braille in O&M—141 of that group were certified in O&M; the remainder identified themselves as having multiple certifications. Further research is needed, especially including more representation of rehabilitation professionals, to obtain more input concerning this controversial topic.